PERSEPSI GURU PAMONG TERHADAP KOMPETENSI MAHASISWA PPL-2 PPKn FKIP UNTAN ANGKATAN 2015 - Robiandi Robiandi; Sulistyarini Sulistyarini; Andang Firmansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract         The study aims to find out about the supervisor teacher’s perception of pancasila education PPL-2’s competence and the citizenship of fkip untan class of 2015 school year 2018/2019. The prolem in this paper is, “ how the supervisor  teacher’s perception of pancasila education  PPL-2’s education and the citizenship of fkip untan class of 2015 school year 2018/2019. The research method used in this study is a descriptive method with a qualitative form of research. The source data of this research is the predetermined supervisor student’s teachers. The data collection techniques used are live interviews and documentation, while the data collection tools used are live interviews and documentation guides. The analyses in this study are presented in qualitative descriptive terms using the three supervisor teachers’ informants. Based on studies it can be concluded that the supervisor teacher’s perception of pancasila’s student teaching PPL-2’s education and the citizenship of the fkip untan class of 2015 school year 2018/2019, is overall quite good, but there are indicators of competence that must be developed and enhanced his understanding and authority. Such as material mastery, variations in learning, comprehension of educational fundamentals, development of curriculum and syllabus. Keywords: Teacher Perception, PPL-2 Student Competence, PPKn.